Effect of diapause status and gender on activity, metabolism, and starvation resistance in the plant bug Lygus hesperus. Issue 2 (2nd July 2013) - Brent, Colin S.; Klok, C. Jaco; Naranjo, Steven E.
Abstract: Lygus hesperus Knight (Hemiptera: Miridae), a key pest species distributed throughout the western USA, survives winter in a state of diapause. A laboratory population was examined to elucidate the changes in behavior and physiology linked to this period of dormancy and to determine how these changes are affected by gender. It was found that under starvation conditions, diapausers lived significantly longer compared to non‐diapausers in both genders. This may be attributable to the greater lipid reserves that diapausers have compared to non‐diapausers. Diapausers also spent more time at rest and less time feeding than non‐diapausers. Gender did not impact these behaviors. There was no difference in resting metabolic rate or flight activity between diapausers and non‐diapausers, however, there were significant gender differences when the data were pooled. Males had higher resting metabolisms than females, whereas females spent more time flying. Collectively, these results point toward a higher degree of resource conservation in diapausers. These differences may enhance resistance to starvation and dehydration conditions that L. hesperus are likely to encounter while overwintering.